The first winter record of Nyctalus noctula in northeastern Ukraine - Merzlikin, I. (Theriologia Ukrainica, 2018)
The common noctule is considered a typical species of migratory bats in the forest-steppe of northeastern Ukraine. In the last few years, the species has shown a tendency to expand its wintering range. Wintering common noctules were recorded throughout Ukraine, including neighbouring with the current record regions. The first record of the species during winter in the territory of Sumy region is noted. The finding of an individual (young male) of the common noctule in the basement of a multi-storey building in Sumy city on 10 January 2017 is described. The present record expands the boundaries of the currently recognized wintering range of the species to 150 km northward and 200 km eastward from other known winter record localities of the species.